Novel electrogram featurization reveals a spectrum of response to ablation from atrial tachycardia to types of atrial fibrillation. (3rd October 2022) - Ganesan, P; Rogers, A J; Deb, B; Feng, R; Ruiperez-Campillo, S; Tjong, F V; Bhatia, N; Clopton, P; Rappel, W J; Narayan, S M
Abstract: Background: Although atrial tachycardia (AT) may interconvert with fibrillation (AF) in many patients, it is undefined if this represents a pathophysiological spectrum of organization, or whether it indicates that AF will respond better to ablation. Objective: To test the hypothesis that the spatial area within which electrograms (EGMs) repeat in synchronized fashion over time indicates a spectrum from AT, in which areas span the entire atria, to AF, in which areas are limited. We further hypothesized that repetitive areas would be larger in AF patients with acute termination than in those with poor response to ablation. Methods: We studied N=234 patients (47% women, 64±10Y), of whom (i) N=10 had AT, (ii) N=120 had AF that terminated with ablation ("Term"), (ii) N=104 had AF that did not terminate ("Non-term"). All patients had global left atrial mapping by 64 pole baskets (Abbott, IL). Spatial areas of repetitive activity (REACT) were calculated by correlating unipolar EGMs in 2x2 grids for 4 sec, repeated for the entire atria (Figure 1A, B). We quantified global organization by averaging the REACT map for each patient. Results: Figure 1C shows progressively decreasing areas of repetitive EGM from AT to AF Term to AF Non-term (p<0.001, ANOVA). Figure 1D shows a case of AT in a 71 YO male and global REACT >0.90, a case of AF REACT 0.45 in a 65 YO male with termination by ablation, and a case of AF with REACT 0.19 in an 85 YO male that did not terminate. Further, ROC analysis of REACT analysis in AF cases predicted termination with an AUC of 0.71. Conclusion: Spatial areas of repeating electrogram shapes indicates a spectrum from AT to AF with good and AF with poor acute response to ablation. Future studies should investigate whether REACT areas can be identified non-invasively, such as by body surface ECG, to guide ablation or prognosis. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): US National Institutes of Health